Efficacy of Silodosin in Expulsive Therapy for Distal Ureteral Stones: A Randomized Double-blinded Controlled Trial - Wang, Chung Jing; Tsai, Po Chao; Chang, Chien Hsing (Urology Journal, 2016)
Purpose: To evaluate the efficacy of silodosin in the medical expulsive therapy for symptomatic distal ureteral stones. Materials and Methods: This prospectively randomized controlled trial was carried out from May 2011 to December 2014. In all, 198 patients with radiopaque distal ureteral stones <10 mm in size were eligible: 61 patients in the control group and 62 patients in the silodosin group. The silodosin group received silodosin 8 mg daily, and the control group received lactose tablets. The primary outcome was the expulsion rate. The secondary outcomes the expulsion time, analgesic consumption, lower urinary tract symptoms, colic episodes, and adverse effects. Statistical analyses were performed using a Mann-Whitney U-test and chi-square test. Results: The final analysis was conducted with 61 control and 62 silodosin patients as the denominator in each randomization arm. The average expulsion times were 6.31 ± 2.13 days for the silodosin group and 9.73 ± 2.76 days for the control group (P < .001). Conclusion: Treatment with silodosin proved to be safe and effective, as demonstrated by the increased stone expulsion rate, the reduced expulsion time, and the reduced analgesics consumption.